Numeric analysis of large penetration of the cone in undrained soil using fem - Markauskas, Darius; Kačianauskas, Rimantas; Katzenbach, Rolf (Journal of Civil Engineering and Management, 2003)
Numeric analysis of the large penetration of the cone in undrained soil using finite element method (FEM) is presented. Until now the computation procedures has not been developed to such an extent, that they could provide numerical solution of large cone penetration problem. In this paper for solving of the large cone penetration problem an updated Lagrangian formulation and finite element method are used. To overcome large distortion of the finite element geometry during cone penetration leading to illconditioning equations a remeshing technique is developed. The proposed remeshing technique enables the simulation of the penetration process until steady cone penetration is reached. The analysis of the cone penetration in undrained soil is provided. The comparison of current numerical results and other authors' results are presented.First Published Online: 26 Jul 2012